The use of strawmix in cattle fattening ration - B. Soewardi; D. Sastradipradja; Suryahadi Suryahadi (Hemera Zoa, 1991)
Two experiments were carried out to study the use of rice straw as the sole source of roughage in ration for cattle fattening. In each experiment 16 heads of young bulls, Frisian Holstein (FH), and Australian Commercial Cross (ACC). were arranged in completely randomized design with 4 different roughages as treatment criteria: (i) elephant grass as control, (ii) unprocessed rice straw, (iii) urea treated rice straw, (iv) CaO traated rice straw. No significant difference in weight gain among treatments in both experiments exist. In the firrst experiment the average daily gain (ADG) for treatment 1, 2, 3 and 4 was respectivelly 0.75, 0.78, 0.89, and 0.78 kg, while in the second experiment the ADG was respectively 0.51, 0.48, 0.71, and 0.62 kg per head per day. On the average the FH bulls performed superior gain of 0.80 kg/head/day while the ACC is moderate (0.58 kg/had/day). In the first experiment no significant difference in dry matter consumption among treatments obtained. In the second experiment the dry matter consumption of elephant grass was lower compared to strawmix. FH bulls show higher consumption of dry matter (3.1% of live weight), while the value of ACC bulls is only 2.5% live weight.  Feed efficiency is not statistically different among treatment in both experiments, namely 9.1, 8.0, 7.4 and 8.4 kg dry matter/kg ADG in the first experiment, and 13.9, 19.6, 11.8, and 14.8 dry matter/kg ADG in the second experiment. FH bulls show higher efficiency of 8.2% while ACC bulls is only 15.0%.